Western firms' successful and unsuccessful business models in China - Gountas, Sandra; Chan, Tysun; Zhang, L.; Handley, Brian (Elsevier, 2016)
The study applies complexity theory to construct and empirically test western firms' successful and unsuccessful business models in the Chinese business environment. Because operating in China consists of a complex whole of business aspects, the study uses a set-theoretic approach to theory construction and testing of alternative operating recipes. Each of the 72 firms is analyzed by firm management demographics and survey respondents for operating in China. Data are scored at the firm level. The findings include presenting complex antecedent configurations; recognizing three relevant simple conditions in a complex configuration (senior manager expediting, knowledge of Chinese business environment, and senior manager ability in obtaining financing). This complex statement indicates high Australian firms' business success in China. The study concludes with a call for western firms to recognize the implicit shift from separately considering conditions of operating in China to integrating antecedent conditions as a whole in order to nurture their business to success.